2006
DOI: 10.1007/s00244-005-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diuron on Aneuploidy and Hemocyte Parameters in Pacific Oyster, Crassostrea gigas

Abstract: Diuron is a substituted urea herbicide used for agricultural and nonagricultural weed control. Its widespread use and relatively slow breakdown led us to analyze its influence on aneuploidy level (lowered chromosome number in a percentage of somatic cells) and hemocyte parameters in Pacific oysters, Crassostrea gigas. Adult oysters were subjected to two diuron concentrations (300 ng L(-1) and 3 microg L(-1)) for 11 weeks. Significantly higher aneuploidy level was observed in diuron-treated oysters compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 46 publications
2
35
0
2
Order By: Relevance
“…In this context, sub-lethal adverse effects need to be more documented through experiments carried out using pesticides at environmentally relevant concentrations. Among studies focused on pesticides, most of them have been carried out by exposing animals to relatively long periods of time (Auffret et Oubella., 1997;Tanguy et al, 2005;Bouilly et al, 2007, Buisson et al, 2008 giving an insight on the effects of chronic exposures on physiological functions of the organism. Nevertheless, it is well known that in natural waters, uneven concentrations of pesticides are found in the water mass because of different factors such as seasonal agricultural practices, weathering processes and peak concentrations are often found in the aquatic environment for short periods of time (Munaron, 2006;Hyne et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, sub-lethal adverse effects need to be more documented through experiments carried out using pesticides at environmentally relevant concentrations. Among studies focused on pesticides, most of them have been carried out by exposing animals to relatively long periods of time (Auffret et Oubella., 1997;Tanguy et al, 2005;Bouilly et al, 2007, Buisson et al, 2008 giving an insight on the effects of chronic exposures on physiological functions of the organism. Nevertheless, it is well known that in natural waters, uneven concentrations of pesticides are found in the water mass because of different factors such as seasonal agricultural practices, weathering processes and peak concentrations are often found in the aquatic environment for short periods of time (Munaron, 2006;Hyne et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similar aneuploidy levels were observed in adults and juveniles. Bouilly et al (2007) showed that the herbicide diuron induced also aneuploidy in adult Pacific cupped oysters after a 11 week exposure period at 300 ng L -1 and 3 µg L -1 . The induced aneuploidy observed appeared to be transmitted to the next generation as offspring exhibited significantly higher aneuploidy levels when their parents had been exposed to diuron (Bouilly et al, 2007).…”
Section: Genotoxicity In Marine Bivalvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouilly et al [44] studied the impact of the herbicide diuron on Crassostrea gigas (Pacific oyster) and observed that the herbicide can cause irreversible damages to the genetic material of the organism studied. Moreover, the authors affirm that, due to the persistence of diuron in environments adjacent to its application site and that it is preferably used in spring, the pollution caused by its use causes negative impact in the aquatic organisms during the breeding season.…”
Section: Aquatic and Soil Contamination Due To The Presence Of Herbicmentioning
confidence: 99%
“…It is not surprising that Diuron alone did not initiate the carcinogenesis process in this organ. Although some reports in the literature suggest that Diuron is genotoxic (Agrawal et al 1996;Agrawal and Mehrota 1997;Bouilly et al 2007), studies developed in our laboratory indicated that the herbicide does not damage DNA in vivo (Nascimento et al (Rocha et al, 2009) when tested by the comet (single cell gel eletrophoresis) assay. Besides, Diuron did not exert initiating or promoting potentials in the skin of Swiss albino mice (Ferrucio et al, 2009).…”
Section: Discussionmentioning
confidence: 93%